Second order generalized invexity and duality in mathematical programming - Mishra S.K. (My University, 2025)
Rueda and Hanson have given sufficient optimality criteria for a nonlinear programming problem by introducing pseudo-type I and quasi-type I functions. Recently Hanson defined second order type-I functions. In this paper, second order pseudo-type I, second order quasi-type I, and their natural generalizations are defined and applied to second order duality results for several mathematical programs.